Estimasi Dampak Urban Heat Island terhadap Laju Evapotranspirasi: Studi Kasus di Kota Palembang: Estimation the Impact of Urban Heat Island on Evapotranspiration Rate: A Case Study in Palembang City - Ari Sugiarto; Budi Indra Setiawan; Chusnul Arif; Satyanto Krido Saptomo (Jurnal Teknik Sipil dan Lingkungan, 2021)
A review of air temperature in the Palembang city by reviewing data from the National Agency for Meteorology, Climatology, and Geophysics/BMKG (Kenten Climatology Station and the SMB II Meteorological Station) shows a difference in air temperature can indicate the occurrence of Urban Heat Island (UHI). The difference in air temperature affects the evapotranspiration rate (ET) because air temperature very influencing water evaporation. ET rate estimation with air temperature data is the first step to prove this hypothesis. Hargreaves and Samani, Blaney and Criddle, Linacre, and Kharuffa models is the ET model that using air temperature as the variable was used to estimate the ET rate. Air temperature data used in the period 2011-2020 by reviewing data from the Kenten Climatology Station and the SMB II Meteorological Station. The results of this study of air temperature data from the Kenten Climatology Station and the SMB II Meteorology Station showed a difference in air temperature with the minimum ∆T of 0.42 oC, the maximum of 0.43 oC, and the daily average of 0.41 oC. This difference in air temperature has an impact on the difference in the ET rate with the average ∆ET of the Hargreaves and Samani model of 0.05 mm/day, the Blaney and Criddle model of 0.05 mm/day, the Linacre model of 0.06 mm/day, and the Kharuffa model of 0.14 mm/day. The results of this study predicted that an increase in air temperature causes an increase in the ET rate of ± 10-30%.